Smad4-deficient T cells promote colitis-associated colon cancer via an IFN-γ-dependent suppression of 15-hydroxyprostaglandin dehydrogenase - Choi, Sung Hee; Huang, Alex Y.; Letterio, John J.; Kim, Byung-Gyu (Frontiers in Immunology, 2022)
Immune cells and the cytokines they produce are important mediators of the transition from colitis to colon cancer, but the mechanisms mediating this disease progression are poorly understood. Interferon gamma (IFN-γ) is known to contribute to the pathogenesis of colitis through immune modulatory mechanisms, and through direct effects on endothelial and epithelial homeostasis. Here we explore whether IFN-γ influences tumor progression by expanding the effector memory T cells (TEM) population and restricting the expression of tumor suppressors in a preclinical model of spontaneous colitis-associated colorectal cancer (CAC). We show that IFN-γ expression is significantly increased both in the T cells and the colonic mucosal epithelia of mice with a T cell-restricted deletion of the TGF-β intermediate, SMAD4 (Smad4TKO). The increase of IFN-γ expression correlates with the onset of spontaneous CAC in Smad4TKO mice by 6 months of age. This phenotype is greatly ameliorated by the introduction of a germline deletion of IFN-γ in Smad4TKO mice (Smad4TKO/IFN-γKO, DKO). DKO mice had a significantly reduced incidence and progression of CAC, and a decrease in the number of mucosal CD4+ TEM cells, when compared to those of Smad4TKO mice. Similarly, the colon epithelia of DKO mice exhibited a non-oncogenic signature with a decrease in the expression of iNOS and p-STAT1, and a restoration of the tumor suppressor gene, 15-hydroxyprostaglandin dehydrogenase (15-PGDH). In vitro, treatment of human colon cancer cells with IFN-γ decreased the expression of 15-PGDH. Our data suggest that Smad4-deficient T cells promote CAC through mechanisms that include an IFN-γ-dependent suppression of the tumor suppressor 15-PGDH.